Waste-Tire-Derived Activated Carbon as Efficient Adsorbent of P-Nitrophenol from Wastewater - Chunhua Hu; Suliu Hu; Ping Fang; Zijun Tang; Xiang Xiao; Haiwen Wu (Journal of Chemistry)
In this work, a two-stage activation method was used to prepare adsorbents from scrap tire rubber. Firstly, KOH was mixed with rubber using different impregnation ratios (1–2) for primary activation; a second activation was performed after pyrolysis at 650°C and 750°C; and finally, the samples were acid-washed using HNO3. The prepared materials were characterized by elemental analysis, nitrogen adsorption isotherms, SEM, FTIR, and XPS. The adsorption capacity and mechanism of these materials on p-nitrophenol in wastewater were also investigated. It was found that after two-stage activation, the specific surface area of the materials can be effectively increased, and the surface of the materials can be enriched with oxygen-containing functional groups. The maximum adsorption capacity of PNP could reach 143.9 mg g−1, which is slightly higher than the literature data under the same conditions. The adsorption process is in the form of chemisorption and is dominated by hydrogen bonding and π-πEDA formation, but the adsorption tends to be monolayer, and the adsorption behavior can be described by a proposed secondary model. In addition, the adsorbent has a stronger adsorption capacity under acidic conditions.